Multiple-ellipse fitting method to precisely measure the positions of atomic columns in a transmission electron microscope image. (October 2018) - Zhang, Q.; Jin, C.H.; Xu, H.T.; Zhang, L.Y.; Ren, X.B.; Ouyang, Y.; Wang, X.J.; Yue, X.J.; Lin, F.
Highlights: We proposed a multiple-ellipse fitting method to accurately determine the atomic column positions in TEM images. This method could achieve precision in the picometre range. Not only the position but also intensity distribution of each atomic column could be obtained in this method. Therefore, the intensities of the neighbouring atomic column could be subtracted for each atomic column during an interactive position refinement. Compared with the model-based method, the multiple-ellipse fitting method is more adaptable since the intensity distribution of each atomic column is not limited to be a Gaussian-shaped function. We quantitatively test our algorithm by analysing an image containing two Gaussian-shaped atoms and some simulated HRTEM images of SrTiO3 . Abstract: In this paper, we propose a multiple-ellipse fitting method to accurately determine the atomic column positions in transmission electron microscopy (TEM) images. The column is enclosed by a series of ellipses fitted from contour lines at equidistant intensity levels, and each atomic column is shaped by an averaged elliptical shape to obtain its positions. In particular, the intensity profile of the atomic column can be obtained by an elliptically rotational average based on its shape; therefore, the intensities of the neighbouring atomic column can be subtracted for each atomic column during subsequent position refinement. This method can achieve precision in the picometre range, and we quantitatively measure this precision by analysing an image containing two Gaussian-shaped atoms and some simulated high-resolution transmission electron microscopy (HRTEM) images of SrTiO3 .